2006
DOI: 10.1167/iovs.06-0376
|View full text |Cite
|
Sign up to set email alerts
|

Microsporidial Keratitis in India: 16S rRNA Gene-Based PCR Assay for Diagnosis and Species Identification of Microsporidia in Clinical Samples

Abstract: This study is the first to validate PCR-based assays for detection of microsporidial DNA in corneal scrapings. Pan microsporidian PCR can be a useful adjunct with smear examination in the diagnosis of microsporidial keratitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 20 publications
1
47
0
Order By: Relevance
“…Nonetheless, PCR allowed the identification of microsporidia in the subspecies level. 19,26 Recently a study showed that 11.4% of patients with microsporidial keratoconjunctivitis have concomitant adenoviral infection. 27 Specific PCR for adenovirus and enterovirus is negative for all of our specimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, PCR allowed the identification of microsporidia in the subspecies level. 19,26 Recently a study showed that 11.4% of patients with microsporidial keratoconjunctivitis have concomitant adenoviral infection. 27 Specific PCR for adenovirus and enterovirus is negative for all of our specimens.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PCR is a sensitive way for organism detection, and subsequent sequencing of PCR products is used to identify particular microsporidial species. 19,20 The use of drugs namely albendazole, fumagillin, itraconazole, and propamidine isethionate has been associated with remission of microsporidial keratoconjunctivitis. However, it has been demonstrated to be less effective in stromal keratitis, in which corneal transplantation is usually required.…”
Section: Introductionmentioning
confidence: 99%
“…Results are excellent on resin embedded sections stained with toluidine blue [31]. Sensitivity of detection by Gram's stain was 90.3%; by Giemsa stain was 64.52% and by modified Ziehl Neelsen stain was 87% as observed by Joseph et al, in their study [32].…”
Section: Other Stains Used For Light Microscopymentioning
confidence: 74%
“…Though this is a rapid and sensitive method it is not specific and many other structures like fungal spores will also fluoresce and may give false positive results [31]. Studies show sensitivity of potassium hydroxide with calcoflour white to be 93.5% [32].…”
Section: Chemofluorescent Agentsmentioning
confidence: 99%
See 1 more Smart Citation